2004
DOI: 10.1002/nme.1055
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modelling of fibre reinforced polymer sandwich panels exposed to heat

Abstract: SUMMARYA finite element model that predicts temperature distribution in a composite panel exposed to a heat source, such as fire, is described. The panel is assumed to be composed of skins consisting of polymer matrix reinforced with fibres and a lightweight core (the paper concentrates on the crucial aspect of the problem, i.e. the behaviour of the 'hot' skin of the panel. The core is assumed not to decompose, and the 'cold' skin is treated exactly as the 'hot' skin.) It is assumed that the polymer matrix und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Fig. 4A and B shows the temperature versus time profiles at x ¼ L S1 /2 as simulated for the cases of 1) an adiabatic lateral surface (ALS), 2) an adiabatic bottom surface (ABS), 3) the absence of surface ablation (NA), 4) the absence of external heat transfer resistance with (NHR) and without (NHRNA) surface ablation and 5) the flame temperature modelled according to the three standards introduced above (the experimental measurements [32] are included for comparison purposes). It can be observed that the effects associated with the lateral and bottom heat losses are negligible with an almost perfect coincidence between the assumption of an adiabatic wall and the results of the reference model.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 4A and B shows the temperature versus time profiles at x ¼ L S1 /2 as simulated for the cases of 1) an adiabatic lateral surface (ALS), 2) an adiabatic bottom surface (ABS), 3) the absence of surface ablation (NA), 4) the absence of external heat transfer resistance with (NHR) and without (NHRNA) surface ablation and 5) the flame temperature modelled according to the three standards introduced above (the experimental measurements [32] are included for comparison purposes). It can be observed that the effects associated with the lateral and bottom heat losses are negligible with an almost perfect coincidence between the assumption of an adiabatic wall and the results of the reference model.…”
Section: Resultsmentioning
confidence: 99%
“…9. Normal stress at the un-exposed face, normalized by r0=e 1=n of chemical decomposition to the thermal distortion requires further investigation using the thermal model which considers the loss of mass and charring [7,8,[15][16][17].…”
Section: Concluding Remarkmentioning
confidence: 99%
“…Several researchers , Henderson & Doherty (1987a), Henderson & Wiebelt (1987b), Florio et al (1989), Sullivan & Salamon (1992a), Sullivan & Salamon (1992b), Perring et al (1980), Mc Manus & Springer (1992a), Mc Manus & Springer (1992b, Dimitrienko (1995), Davies et al (1995a) Dimitrienko (1997), Milke & Vizzini (1991), Gibson et al (1995), Davies & Wang (n.d.), Looyed et al (1997), Gibson et al (2004), Lattimer & Ouelette (2006), Trelles & Lattimer (2007)] have developed different approaches but the most influential work in this area came from Henderson et al (1985). Research on the effects of fire on sandwich composite has used the same principle as single monolithic composite in terms of modelling [Davies et al (1995a), Davies et al (1995b), Looyed et al (2001), Krysl et al (2004), Galbano et al (n.d.), Marquis (2010a)]. In all of these cases, some assumptions are made.…”
Section: Modelling Physical Transport Processes In Solid Phase Duringmentioning
confidence: 99%